2019
DOI: 10.5430/ijhe.v9n1p189
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Principal’s Distributed Leadership Practice on Students’ Academic Achievement: A Systematic Review of the Literature

Abstract: Distributed leadership as a new scenario of educational leadership has become a popular topic in the contemporary world. Many notable researchers and members of the discourse community have contributed significantly to its development. However, little attention has paid to its effectiveness. Hence, the main purpose of this article is to analyze the existing evidence for the effect of principal’s leadership practice on students’ academic achievement from a distributed perspective. To do so, a systematic search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…The findings showed that school administrators are satisfied with the performances of teachers who are not formal leaders but are assigned leadership responsibilities implying that spreading over leadership positively impacts school effectiveness. This is similar to the findings of a systematic review of the literature on the effect of principals' distributed leadership practice on students' academic achievement by Daniel and Lei (2019). They concluded that distributed leadership becomes effective when school administrators encourage "shared vision, shared power, enable others to act, focus on capacity building and involve others in decision-making" (Daniel & Lei, 2019, p.195).…”
Section: "No You Can't Do All Things Alone; You Have To Designate You...supporting
confidence: 65%
“…The findings showed that school administrators are satisfied with the performances of teachers who are not formal leaders but are assigned leadership responsibilities implying that spreading over leadership positively impacts school effectiveness. This is similar to the findings of a systematic review of the literature on the effect of principals' distributed leadership practice on students' academic achievement by Daniel and Lei (2019). They concluded that distributed leadership becomes effective when school administrators encourage "shared vision, shared power, enable others to act, focus on capacity building and involve others in decision-making" (Daniel & Lei, 2019, p.195).…”
Section: "No You Can't Do All Things Alone; You Have To Designate You...supporting
confidence: 65%
“…According to Spillane ( 2005 ), it is used interchangeably with ‘shared leadership,’ ‘collaborative leadership,’ ‘delegated leadership,’ and ‘dispersed leadership.’ In all cases, this leadership model is not restricted in one figure in the school, but rather dispersed to include staff at all levels (Harris, 2013 ; Thien & Chan, 2022 ). It has to do with power sharing (Hatcher, 2005 ; Özdemir et al, 2022 ), empowering staff (Jambo & Hongde, 2020 ), and building the capacity for improvement (Carrington et al, 2022 ; Harris, 2013 ).…”
Section: Prominent Leadership Models In Educational Researchmentioning
confidence: 99%
“…A growing body of literature acknowledges a crucial role of distributed leadership for successful innovations in schools (Brown et al, 2020;Daniëls et al, 2019;Fullan, 2016;Hulpia et al, 2009;Jambo & Hongde, 2020;Law et al, 2010;Meijer, 2014;Ricard et al, 2017;Sullivan et al, 2012;Tian et al, 2016;Tummers & Knies, 2013;Vogel & Masal, 2015). This is in line with the international call for a more social, collaborative, and networked approach to school innovations .…”
Section: Introductionmentioning
confidence: 91%
“…Lastly, several review studies indicate that the leadership role of school principals and their background characteristics are key to creating conditions for distributed leadership practices (Drewes et al, 2019;Jambo & Hongde, 2020;Liu et al, 2018;März et al, 2018;Tian et al, 2016). However, the ways in which school principals' leadership foster distributed leadership practices is relatively understudied (Drewes et al, 2019;Mentink et al, 2021).…”
Section: School Context Level Linked To Distributed Leadership Practicesmentioning
confidence: 99%
See 1 more Smart Citation